- Thread starter wrifalon
- Start date

wrifalon said:2x+(6-x)/3=-3

i get this

2x+(6/3-1/3x=-3: NO! Multiply by 3 to get 6x + 6 - x = -9 (if you don't follow that, see your teacher!)

Start from where Denis corrected your calculations: After multiplying each term by 3, you get

6x + 6 - x = -9

Combining like terms on the left: 5x + 6 = -9

Subtracting 6 from both sides: 5x = -15

Dividing by 5: x = -3

Check:

2(-3) + (6-[sup:sv19tttr]-[/sup:sv19tttr]3)/3 = -3

-6 + 9/3 = -3

-6 + 3 = -3

-3 = -3

- Joined
- Jun 18, 2007

- Messages
- 18,135

wrifalon said:2x+(6-x)/3=-3 The (6-x)/3 is a fraction (6-x) in the numerator and the 3 is on the bottom.

i get this

2x+(6/3-1/3x=-3

5/3x+6/3=-3

5/3x=-5<<<<< Right after this - you went wrong

(5/3)* x * (3/5) = -5 * (3/5) <<<<< multiply by 3/5 both sides - to isolate 'x'

x = - 3

You check your answer - by putting it into the original equation:

2x + (6 - x)/3 = 2*(-3) + [6 -(-3)]/3 = -6 + 9/3 = - 6 + 3 = -3 <<<< checks